Analysis of molecular targets and mechanisms of Bisphenol F (BPF)-induced non-alcoholic fatty liver disease (NAFLD) based on network toxicology and molecular dynamics - Riwei Wang; Qiangming Liao; Xianwei Liu; Liang Sun; Yun Xia (PLoS ONE, 2026)
Bisphenol F (BPF), a primary substitute for bisphenol A (BPA), is widely utilized in industrial production and daily life. However, its widespread environmental presence has raised concerns regarding potential health risks. This study aims to investigate the potential toxic targets of BPF in the pathogenesis of non-alcoholic fatty liver disease (NAFLD). Initially, potential target genes of BPF were identified using the ChEMBL, STITCH, and SWISS databases. NAFLD-related genes were obtained from the OMIM and GeneCards databases, yielding a preliminary set of 28 overlapping candidate targets. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were subsequently performed to elucidate the biological processes and signaling pathways potentially affected by BPF. Differential expression analysis of transcriptomic data from NAFLD and normal liver tissues obtained from the GEO database (GSE260666) revealed that CYP2C19 and SHBG were significantly upregulated in NAFLD samples, suggesting their potential as key targets of BPF. Molecular docking simulations using AutoDock demonstrated stable binding conformations between BPF and both CYP2C19 and SHBG proteins, with favorable binding free energies indicating strong interactions. Furthermore, molecular dynamics simulations confirmed the structural stability of the protein-ligand complexes under simulated physiological conditions. These findings provide a theoretical basis for understanding the toxic targets and mechanisms of BPF in NAFLD pathogenesis and offer insights for the prevention and treatment of NAFLD associated with BPF exposure from plastic products.